Body Perception and Organ Donation: Bereaved Parents' Perspectives. (September 2019) - Mahat-Shamir, Michal; Hamama-Raz, Yaira; Leichtentritt, Ronit D.
The view of the body in sociological, psychological, and gender studies may be broadly summarized to three metaphors: (a) the body as a machine, (b) the body as Self, and (c) the body as sacred and sanctified entity. Each of these philosophical views has an impact on organ donation. The current study aimed at revealing body perception of bereaved Israeli parents who agreed to donate organs of their deceased child. A deductive and inductive thematic analysis captured an ongoing perceptual change that bereaved donor parents experienced in their view of the child's body. Parents' ability to move between two positions (the body as Self, the body as a machine) allowed them to agree with and protect their decision to donate as well as to maintain an ongoing bond with their deceased child. The view of the body as scared entity was not evident in the bereaved parents' narratives.